Omani-italian archaeological expedition at al tikha (2023) - Douglas, Khaled; Pizzimenti, Sara (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Omani-Italian Archaeological Expedition at Al Tikha, a joint project between the Sultan Qaboos University and the University of Pisa started in 2022 with the aim to investigate the archaeological site of Al Tikha, strategically located in the Batinah plain, near modern city of Al Rustaq. The 2023 excavation season focused on seven distinct areas: settlements (Mound A, Mound B, Building S1, Building S2), a metallurgical site (Mound C), and the necropolis (T1, T2).
Keywords: Archéologie -- Oman

Sultan qaboos university project in oman (2022): Discovery of an early bronze age settlement in al ghoryeen, mudhaybi, sultanate of oman - Jahwari, Nasser Said al-; Douglas, Khaled; Hesein, Mohamad (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The Department of Archaeology at Sultan Qaboos University (SQU), in collaboration with the Ministry of Heritage and Tourism (MHT), has conducted the 3rd season (December 2022) of intensive excavations at the site of Al Ghoryeen in Wadi Andam region on the southern fringes of the eastern Hajar Mountains in the Northern Al Sharqiyah Governorate of Oman. It was excavated under the direction of Professor Nasser S. Al-Jahwari and Dr Khaled Douglas. Participants included colleagues and MA students from the Department of Archaeology at SQU (Dr Mohamad Hesein, Dr Nasser Al-Hinaei, Yaqoob Al-Rahbi, Yaqoob Al-Bahri, Al-Reem Al-Alawi, Suad Al-Harasi, Wajd Al-Zakwani, Buthainah Al-Ghofaili and Huda Al-Daihani) and the German Archaeological Instiute in Berlin (represented by Dr Kristina Pfeifer). The results of the excavation discovered the first and largest settlement in Oman dating back to the Early Bronze Age of Hafit period (ca. 3400-2700 BC).
Keywords: Archéologie -- Oman